Prevalence of lameness in cattle in selected areas of Bangladesh - Ali, ML; Hasan, M; Miah, MAH; Hanif, SM; Juyena, NS; Hashim, MA (Bangladesh Veterinarian, 2018)
Prevalence of lameness was investigated in 1000 randomly selected cattle in Veterinary Teaching Hospital, Bangladesh Agricultural University (BAU) and different dairy farms in Boira Union, Mymensingh during January to December 2015. The aetiology, age [Cal≤f 1 year, 1 - 3 years, 3 - 5 years and >5 years], sex (male, female), different stages of cattle [Calves, Heifers, Pregnant cows, Lactating cows, Dry cows, and Bulls] and floor type (concrete, muddy floor, pavement, straw yard) were studied. Out of 1000 cattle examined, 111 (11.1%) showed lameness in different grades, with 82.0% slightly, 14.4% moderately and 3.6% severely lame. The aetiologies of lameness are upward fixation of patella, traumatic injury, foot and mouth disease (FMD) complications, arthritis, interdigital hyperplasia, interdigital dermatitis and interdigital necrobacillosis. Higher percentages of lameness were in hind limbs than fore limbs. Left hind limbs were more frequently affected than right hind limbs. Animals over 5 years of age were most vulnerable to lameness. Female especially high yielding cows were at higher risk (69.4%) than the male cattle (30.6%). Prevalence of lameness was higher when cattle were confided to the concrete floor than the muddy floor. Pregnant cows were the most vulnerable to lameness. It is suggested that aetiology, age, sex, different stages of cattle and floor type could be considered as risk factors causing lameness in cattle. Bangl. vet. 2017. Vol. 34, No. 1, 1-8